2016
DOI: 10.1002/jmv.24646
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus detection in multiple sclerosis patients under natalizumab therapy: Profile and frequency of urinary shedding

Abstract: Patients undergoing Natalizumab (NTZ) therapy are at risk of progressive multifocal leukoencephalopathy (PML). Besides John Cunningham virus (JCV), BK polyomavirus might represent an additional concern for such patients since it can also infect CNS cells. Currently, data regarding the presence of anti-JCV antibodies added to previous immunosuppressive therapy and prolonged NTZ therapy has been used to classify patients at risk of developing PML. Here, we investigated the profile shedding of JCV and BKV in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…CSF from 10 MS patients were negative for HPyV6 and HPyV7 DNA [42], suggesting that reactivation of these two HPyVs may be a rare event in MS patients. Studies by several groups have shown that BKPyV, JCPyV or both can be detected in urine from MS patients receiving natalizumab or β-interferon [76][77][78][79][80][81], indicating that HPyV viruria is not uncommon in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…CSF from 10 MS patients were negative for HPyV6 and HPyV7 DNA [42], suggesting that reactivation of these two HPyVs may be a rare event in MS patients. Studies by several groups have shown that BKPyV, JCPyV or both can be detected in urine from MS patients receiving natalizumab or β-interferon [76][77][78][79][80][81], indicating that HPyV viruria is not uncommon in these patients.…”
Section: Discussionmentioning
confidence: 99%
“… 267 Analysis of serum‐derived EV microRNAs also demonstrated that a variety of microRNAs were associated with MS recurrence and activity, 264 , 268 , 269 and can be used to support personalized treatment decisions. Exosomes are also used in the diagnosis and monitoring of immune disorders such as multifocal leukoencephalopathy (PML), 270 Sjögren's syndrome, 271 autoimmune skin diseases, 272 IgA neuropathies, 273 adult myasthenia gravis, 274 and inflammatory bowel disease. 275 , 276 …”
Section: Exosome Biomarkersmentioning
confidence: 99%
“…Indeed, Giovannelli and collaborators detected, for the first time, both JCPyV miRNAs not only in blood cells but also in urinary and plasmatic EVs of patients at risk of progressive multifocal leukoencephalopathy (PML) versus HC. The reactivation of JCPyV, causing PML, represents a concrete risk of MS patients under natalizumab treatment [ 81 ]. Therefore, this finding could conceal a repression mechanism of viral replication during the asymptomatic phase of JCPyV.…”
Section: Evs’ Cargo: Reservoir Of Potential Biomarkers For Msmentioning
confidence: 99%